Effects Of Seeding Density And Watering Duration On Sprouting Atmosphere, Quality Characteristics And Antioxidants Of Black Gram (Vigna Mungo L.) Sprouts - Choon, Sea Yeat (2010)
A modified atmosphere containing low oxygen and high carbon dioxide in the sprouting environment could be used to regulate sprouts growth. By manipulating the seeding density and watering duration, the gases atmosphere can be changed. A study on sprouting atmosphere, morphological and chemical characteristics, and phytochemical contents of Vigna mungo sprouts grown in a hermatically sealed chamber was conducted using three seeding densities (75, 100 and 125 g seeds L-1) and three watering durations (10, 15 and 20 min with 3 h interval). The experiment was conducted in a RCBD in split-plot arrangement with watering duration as main plot and seeding density as sub-plot in three replications. Seeds were presoaked in 150 mg Ca L-1 for 12 h and put into a pot and the pot was placed into the hermatically sealed chamber to sprout for 96 h. Sprouting atmosphere in the chamber was measured every 12 h throughout the sprouting period to determine the production of carbon dioxide and ethylene gas. Hypocotyl and root length, hypocotyl diameter, sprout and cotyledon fresh weights, soluble solids concentration, titratable acidity and pH were measured to determine morphological and chemical characteristics of sprouts. Ascorbic acid, total phenolic compounds and antioxidant activities were analyzed to determine phytochemical contents and antioxidant activities of sprouts produced. There were significant (P<0.05) interaction effects of seeding density and watering duration on sprouting atmosphere, morphological and chemical characteristics, and phytochemical contents of sprouts produced. For sprouts that were produced at 75, 100 and 125 g seeds L-1, carbon dioxide production rate showed linear decreases as sprouting progressed. There was a gradual increase of ethylene production rate from 12 to 60 h after imbibition followed by a decrease until the day of harvest. The sprouting atmosphere modified by different seeding density and watering duration created a modified atmosphere that can be used to regulate sprouts growth. At higher seeding densities, hypocotyl and root length decreased as watering duration increased. Hypocotyl diameter of sprouts produced at 100 g seeds L-1 increased as watering duration increased. However, for sprouts that were produced at 75 and 125 g seeds L-1, maximum hypocotyl diameter was produced at 15 min/3 h watering duration and decreased at 20 min/3 h watering duration. Increased in seeding density and watering duration increased the soluble solids concentration, ascorbic acid content and total phenolic compounds of sprouts produced. Optimum water volume that was suitable for best sprouts growth was at 15 min/3 h watering duration. Too much watering reduced the soluble solids concentration, ascorbic acid content and total phenolic compounds at higher seeding density used. Sprouts produced at 100 g seeds L-1 and 15 min/3 h watering duration had the highest percentage of soluble solids concentration, ascorbic acid content and total phenolic compounds. Thus, by regulating seeding density and watering during sprouting, healthy sprouts with acceptable appearance could be produced without the use of chemicals.